PKM2 allosteric converter: A self-assembly peptide for suppressing renal cell carcinoma and sensitizing chemotherapy. (May 2023) - Wang, Lu; Fu, Bo; Hou, Da-Yong; Lv, Yu-Lin; Yang, Guang; Li, Cong; Shen, Jia-Chen; Kong, Bin; Zheng, Li-Bo; Qiu, Yu; Wang, Hong-Lei; Liu, Chen; et al.
Abstract: Stronger intrinsic Warburg effect and resistance to chemotherapy are the responses to high mortality of renal cell carcinoma (RCC). Pyruvate kinase M2 (PKM2) plays an important role in this process. Promoting PKM2 conversion from dimer to tetramer is a critical strategy to inhibit Warburg effect and reverse chemotherapy resistance. Herein, a PKM2 allosteric converter (PAC ) is constructed based on the " in vivo self-assembly" strategy, which is able to continuously stimulate PKM2 tetramerization. The PAC contains three motifs, a serine site that is protected by enzyme cleavable β-N-acetylglucosamine, a self-assembly peptide and a AIE motif. Once PAC nanoparticles reach tumor site via the EPR effect, the protective and hydrophilic β-N-acetylglucosamine will be removed by over-expressed O -GlcNAcase (OGA), causing self-assembled peptides to transform into nanofibers with large serine (PKM2 tetramer activator) exposure and long-term retention, which promotes PKM2 tetramerization continuously. Our results show that PAC -induced PKM2 tetramerization inhibits aberrant metabolism mediated by Warburg effect in cytoplasm. In this way, tumor proliferation and metastasis behavior could be effectively inhibited. Meanwhile, PAC induced PKM2 tetramerization impedes the nuclear translocation of PKM2 dimer, which restores the sensitivity of cancer cells to first-line anticancer drugs. Collectively, the innovative PAC effectively promotes PKM2 conversion from dimer to tetramer, and it might provide a novel approach for suppressing RCC and enhancing chemotherapy sensitivity.